SOSIALISASI METODE PEMBELAJARAN INOVATIF UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI KELOMPOK B DI TK YAPIS MERAUKE BAGI GURU PG-PAUD - Hariani Fitrianti; Ferry Irawan; Beatus Tambaip (Pusat Riset dan Inovasi Nasional, 2022)
Early childhood education has strategies or learning models that must be mastered by teachers. The learning models include the center model, the classic model, the group model, the area model, and many other learning models. To create a fun learning model is part of the task of principals and educators. Over time, the world of education has developed very rapidly. The service method used is socialization, related to the importance of early childhood education as the basic foundation used to monitor children's growth and development. Therefore, teachers must be able to prepare a variety of creative and innovative learning in order to achieve educational goals well. Educators need to make an update in the learning process, especially at the level of children's education. The results show that the world of children is identical to learning activities while playing. So, educators must be able to create creative and innovative learning models. So, early childhood is not easily bored and bored to take part in learning activities